Understanding deforestation lock-in: Insights from Land Reform settlements in the Brazilian Amazon - Russo Lopes, Gabriela; Bastos Lima, Mairon G. (Frontiers in Forests and Global Change, 2022)
Cropland and pasture expansion continues to erase natural ecosystems at a staggering speed globally, notably in the tropics. Conventional policy approaches, usually focused on a particular land-use change driver (e.g., specific commodities) or individual regulations (e.g., the Amazon Soy Moratorium), have consistently failed to achieve sufficient or sustained results. The swift reversal of Brazil’s earlier success in reducing Amazon deforestation – now again accelerated – offers perhaps the most sobering illustration of that. Therefore, this article draws from scholarship on sustainability transitions to propose a more comprehensive systems view of unsustainable land-use patterns. We examine persistent tropical deforestation as a case of “lock-in,” using a transitions lens, and explore its constitutive elements. As a case study, we analyze the situation of Land Reform settlements in the Brazilian Amazon, where as much as one-third of that biome’s deforestation takes place. While subject to some specific factors, those places are also enmeshed in a broader setting that is common across the Brazilian Amazon’s deforestation frontier (e.g., infrastructure conditions, market demands, sociocultural norms). Drawing from document analysis of Brazilian policies and fieldwork in three Land Reform settlements in Pará State, we expose multiple forms of techno-economic, institutional, and socio-cognitive lock-in that together drive deforestation systemically in those settlements. Those drivers form a strongly consolidated socio-technical regime around large-scale agriculture that includes material and immaterial factors (e.g., cultural ones), a regime that not only resists change but also – like a vortex – pulls others into it. Escaping deforestation lock-in may thus require outside forces to help local actors destabilize and eventually replace this unsustainable land use regime. International zero-deforestation efforts offer a starting point, but a transition requires moving beyond piecemeal, incremental change or end-of-pipe approaches and toward concerted, strategic action that addresses multiple of those regime elements in a coordinated way to replace it as a system. We argue that understanding deforestation lock-in is vital for tackling its worrisome persistence and that sustainability transitions theory offers an illuminating, but still underutilized, framework to analyze and eventually overcome unsustainable land use.